Loss of ATG5 impairs CD4+ T cell activation and promotes anti-tumor responses - Plaza-Sirvent, Carlos; Bessen, Clara; Bronietzki, Alisha W.; Klages, Katjana; Schuster, Marc; Huehn, Jochen; Schmitz, Ingo (Frontiers in Immunology, 2025)
Macroautophagy (hereafter called autophagy) is an ancient catabolic process that delivers bulky cargo to lysosomal degradation. The autophagic pathway is regulated by autophagy-related (ATG) proteins that govern the formation of double-membraned vesicles called autophagosomes. Autophagy has been shown to be important for T cell survival and proliferation. However, all studies performed so far used genetic models, in which deletion of an essential Atg gene occurs at early stages of thymic T cell development, raising the question whether developmental defects account for the phenotypes observed in mature T cells. Especially regarding CD4+ T helper cells, little is known about the function of autophagy in specific subsets. Therefore, we generated mice that lack Atg5, an essential component of the core autophagy machinery, in activated CD4+ T cells using OX40-Cre mice. As expected, thymic T cell development was unaffected in these mice. Despite impaired CD4+ T cell activation, Atg5ΔOX40 mice developed lymphadenopathy and exhibited increased T cell numbers, pointing to a defect in immune regulation. Accordingly, frequencies of Foxp3+ regulatory T (Treg) cells were decreased. While activation-induced cell death and in vitro suppressive activity of Treg cells were not affected, ATG5 deficiency in CD4+ T cells led to increased anti-tumor responses against melanoma. In conclusion, our data suggest that ATG5 is crucial for the functional properties of CD4+ T cells and the homeostasis of Treg cells.